Transcriptomic Analysis Reveals the Molecular Mechanisms of Drought-Stress-Induced Decreases in Camellia sinensis Leaf Quality - Wang, Weidong; Xin, Huahong; Wang, Mingle; Ma, Qingping; Wang, Le; Kaleri, Najeeb A.; Wang, Yuhua; Li, Xinghui (Frontiers in Plant Science, 2016)
The tea plant [Camellia sinensis (L.) O. Kuntze] is an important commercial crop rich in bioactive ingredients, especially catechins, caffeine, theanine and other free amino acids, which the quality of tea leaves depends on. Drought is the most important environmental stress affecting the yield and quality of this plant. In this study, the effects of drought stress on the phenotype, physiological characteristics and major bioactive ingredients accumulation of C. sinensis leaves were examined, and the results indicated that drought stress resulted in dehydration and wilt of the leaves, and significant decrease in the total polyphenols and free amino acids and increase in the total flavonoids. In addition, HPLC analysis showed that the catechins, caffeine, theanine and some free amino acids in C. sinensis leaves were significantly reduced in response to drought stress, implying that drought stress severely decreased the quality of C. sinensis leaves. Furthermore, differentially expressed genes (DEGs) related to amino acid metabolism and secondary metabolism were identified and quantified in C. sinensis leaves under drought stress using high-throughput Illumina RNA-Seq technology, especially the key regulatory genes of the catechins, caffeine, and theanine biosynthesis pathways. The expression levels of key regulatory genes were consistent with the results from the HPLC analysis, which indicate a potential molecular mechanism for the above results. Taken together, these data provide further insights into the mechanisms underlying the change in the quality of C. sinensis leaves under environmental stress, which involve changes in the accumulation of major bioactive ingredients, especially catechins, caffeine, theanine and other free amino acids.